Pemanfaatan Fermentasi Eceng Gondok (Eichhornia crassipes) sebagai Pupuk Organik Cair di Dusun Kutu, Desa Segodobancang, Sidoarjo: Utilization of Water Hyacinth (Eichhornia crassipes) Fermentation as Liquid Organic Fertilizer in Dusun Kutu, Desa Segodobancang, Sidoarjo - Pratiwi, Esti Rizkiana; Kurniawan, Muhammad Abdillah; Auliya, Alvin Riss; Cahyaningtyas, Wulan; Rahma, Fitri Aulia; Diamond A. P., Alfa Ridzky (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Dusun Kutu is an area surrounded by tidal swamp land. Approximately 80% of the tidal swamp land is used by the community for rice farming. The area around the farm is overgrown with water hyacinth weed (Eichhornia crassipes), which hurts the environment and society. One effort to overcome this problem is to process water hyacinth into liquid organic fertilizer (POC). The Service Team, consisting of lecturers and UMAHA KKN-T students, made this fertilizer as a program to overcome and reduce environmental problems related to water hyacinth. This program is implemented by making water hyacinth POC through a fermentation process with the addition of EM4 and a brown sugar solution. Then, POC products were socialized regarding the use of water hyacinth as a liquid organic fertilizer in the Dusun Kutu Community. The service team succeeded in making a POC with the main ingredient being water hyacinth and providing education on how to make and use it to the community around Dusun Kutu.